2014
DOI: 10.1371/journal.pbio.1001820
|View full text |Cite
|
Sign up to set email alerts
|

Coronin 1 Regulates Cognition and Behavior through Modulation of cAMP/Protein Kinase A Signaling

Abstract: The evolutionarily conserved protein coronin 1 is needed for activating the cyclic AMP signaling pathway in the brain and is important for cognition and behavior.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(94 citation statements)
references
References 89 publications
2
92
0
Order By: Relevance
“…However, based on our data obtained with T cell-specific Coro1A-deficient mice, we exclude that neuronal Coro1A plays any role in neuronal pathology and axonal injury, which was not very likely. Furthermore, in both mice and humans, a lack of functional Coro1A causes severe neurobehavioral defects, including social deficits, increased aggression, and learning disabilities (26,33). We observed that, in contrast to conventional Coro1a-deficient mice, Cd4-cre ϫ coro1a flox/flox did not display enhanced aggression, which is consistent with the specific absence of Coro1A from T cells (data not shown).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…However, based on our data obtained with T cell-specific Coro1A-deficient mice, we exclude that neuronal Coro1A plays any role in neuronal pathology and axonal injury, which was not very likely. Furthermore, in both mice and humans, a lack of functional Coro1A causes severe neurobehavioral defects, including social deficits, increased aggression, and learning disabilities (26,33). We observed that, in contrast to conventional Coro1a-deficient mice, Cd4-cre ϫ coro1a flox/flox did not display enhanced aggression, which is consistent with the specific absence of Coro1A from T cells (data not shown).…”
Section: Discussionsupporting
confidence: 83%
“…This difference might be attributed to the slightly less efficient deletion of Coro1A expression in CD8 ϩ than CD4 ϩ T cells. Besides its primary expression in the hematopoietic lineage, Coro1A was also detected in neuronal tissue (33,34). However, based on our data obtained with T cell-specific Coro1A-deficient mice, we exclude that neuronal Coro1A plays any role in neuronal pathology and axonal injury, which was not very likely.…”
Section: Discussionmentioning
confidence: 77%
“…Multiple previous studies showed an essential role of profiling in long-term potentiation, associated cytoskeletal rearrangement, and importance in memory (127)(128)(129). Involvement of coronin in regulation of synaptic plasticity and cognition was also confirmed (130). Despite the robust network, observation of mild expression level changes indicate that during persistence of memory minor re-arrangement of cytoskeletal components of cellular and synaptic structures may still occur.…”
Section: Discussionmentioning
confidence: 66%
“…Recent research has implicated the cyclic adenosine monophosphate-protein kinase A-cAMP response elementwww.impactjournals.com/oncotarget/ Oncotarget, Advance Publications 2017 binding protein (cAMP-PKA-CREB) pathway as a key signaling pathway affecting the formation of cognitive function and memory in animals [20][21][22]. This G-coupled receptor signaling pathway involves the activation cAMP which activates PKA and leads to the phosphorylation of CREB.…”
Section: Atrazinementioning
confidence: 99%